The Validity of Indonesian Language Teaching Materials through Audio-Based Islamic Stories in Integrated Islamic Primary Schools - Wais Al Qarni; Rosdiana Rosdiana; Mirnawati Mirnawati; Nurdin K. (Didaktika: Jurnal Kependidikan, 2021)
This study aims to develop audio-based Islamic story teaching materials in valid Indonesian class III learning using the 4-D research model, which includes four stages, namely: define, design, develop, and disseminate (deployment). The subjects of the trial were 24 students in class III SDIT Al-Bashirah, Palopo city. This study indicates that the teaching materials through audio-based Islamic stories are valid by three validators with several revisions through comments and suggestions from the validators. Recapitulation of the score of the validity of the teaching materials obtained was 0.67. The Aikens coefficient value ranges from 0-1 coefficient of 1 (item 1), and others are considered to have adequate content validity (valid).